MEMAKNAI KEMBALI KONSTITUSI KITA (Holisme Pembangunan Hukum di Indonesia) - Otje Salman; Anthon F. Susanto F. Susanto (Sosiohumaniora, 2005)
The development of law in Indonesia presently has entered the transition period, that is, turning into paradigmatic law development, which is based on authority, directing to emansipative law. This kind of position demands some sort of enthusiasm to reinterpret our constitution, because basically as quoted from Hegel’s philosophy, constitution is the “spirit” that will be capable of leading this nation to get out of the crises, particularly crises of confidence in law. As the “spirit”, constitution has consequently to be correctly comprehended through the concept based on goodness, wisdom and justice, not on the contrary like evil (wickedness), power and greed. Only with creativity and wisdom, our constitution can be understood more holistically